Why are you late?: cross-cultural pragmatic study of complaints in American English and Ukrainian - Prykarpatska, Iryna (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2008)
This article examines culture-specific differences in the way a sample of native speakers of American English and Ukrainian make a complaint to their friends. The communication behaviour of both groups of respondents is analyzed within the models of their respective cultures. The research is based on empirical data collected with the help of a questionnaire.